2013
DOI: 10.1055/s-0033-1348896
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in the Pathogenesis and Clinical Manifestations of Uterine Leiomyoma

Abstract: Uterine leiomyomas are the most common benign gynecologic condition. The prevalence is three times more common among women of African ethnicity. Disparity in this disease is evidenced by earlier age of onset, greater severity of symptoms, and different response to treatment. Although the pathogenesis of disease development is not completely known, growing evidence focuses on investigating the molecular mechanisms in disease development and the influence of ethnicity. Variation in the expression levels or funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 127 publications
(121 reference statements)
3
71
0
Order By: Relevance
“…This was followed by two other major studies including a cohort of women from the eastern United States in 2013 by Baird and colleagues (140) and another cohort of Italian women in 2013 by Paffoni and colleagues (141). The high prevalence of vitamin D deficiency in African Americans may explain, at least in part, the high prevalence of uterine fibroids in this patient population (142).…”
Section: Vitamin D Signalingmentioning
confidence: 97%
“…This was followed by two other major studies including a cohort of women from the eastern United States in 2013 by Baird and colleagues (140) and another cohort of Italian women in 2013 by Paffoni and colleagues (141). The high prevalence of vitamin D deficiency in African Americans may explain, at least in part, the high prevalence of uterine fibroids in this patient population (142).…”
Section: Vitamin D Signalingmentioning
confidence: 97%
“…The high prevalence (70%-80%) and presence of accompanying morbid symptoms that affect women with this disease justify the need for improved therapeutic intervention (3). African American women are particularly affected by this disease and experience more severe symptomatology when compared with other women in the population (4)(5)(6)(7). Common symptoms that may afflict these patients and affect their quality of life may include heavy and prolonged menstrual bleeding resulting in anemia, infertility, and pelvic and leg pain (2,4,6).…”
mentioning
confidence: 99%
“…African American women are particularly affected by this disease and experience more severe symptomatology when compared with other women in the population (4)(5)(6)(7). Common symptoms that may afflict these patients and affect their quality of life may include heavy and prolonged menstrual bleeding resulting in anemia, infertility, and pelvic and leg pain (2,4,6). Although hysterectomy is curative, it is associated with short-term and long-term morbidity and precludes future childbirth.…”
mentioning
confidence: 99%
“…Although there are many factors associated with an increased risk of UF development, such as nulliparity, early menarche, obesity and genetics, the race is considered to be one of the most important among them. We have reported that the estimated prevalence of UFs remains significantly higher in African-American women even after controlling for potential confounders such as parity and body mass index 1. These minority women also commonly suffer from vitamin D deficiency 2.…”
Section: Introductionmentioning
confidence: 92%